Philosophical Framework for Human Rights Law and Their Development - Stępkowski, Aleksander (The Universal Protection of Human Rights, 2026)
Abstract: The chapter provides analysis of the concept of human rights considered as the rights of a subject (subjective rights). It describes its emergence in 17 c. as well as further development of the construction, explaining why it is dubious to attribute emergence of rights in ancient times or in Middle Ages. Controversy between naturalistic and positivistic approach towards human rights is also discussed and explained along with the theory of will and that of interest. The chapter proposes to consider human rights as legal description of conditions considered to be necessary for development and flourishing of human being, providing it is understood as individual. This anthropological reservation is of fundamental importance as the philosophical concept of man determines the way we understand conditions enabling human life and development; hence it determines identity of the rights’ concept as well as course of its evolution. Contemporary postmodern transgressions in this respect are also addressed, and it is discussed if the controversial developments of human rights, are to be considered as minor deviations from the generally sound idea, or should they be attributed to intrinsic deficiency of that concept, rising doubts as to the correctness of individualistic anthropology.Keywords: human rights, subjective rights, natural rights, legal rights, theory of will, theory of interest, person, non-human person